Lexical and grammatical categories of nouns - Ochildieva Kh.G (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
is an independent part of speech that combines words denoting objects and animate beings (the meaning of objectivity) and answering the questions who? what? This meaning is expressed using the independent categories of gender, number, case, animateness and inanimateness. In a sentence, nouns mostly act as subject and object, but they can also be other members of the sentence.